2006
DOI: 10.1378/chest.129.6.1441
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Severe Acute Respiratory Syndrome With Glucosteroids

Abstract: This Guangzhou retrospective study revealed that proper use of corticosteroid in confirmed critical SARS resulted in lowered mortality and shorter hospitalization stay, and was not associated with significant secondary lower respiratory infection and other complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
264
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(277 citation statements)
references
References 26 publications
2
264
0
7
Order By: Relevance
“…In a retrospective study of patients with SARS-CoV and sepsis, steroids, in a mean daily dose of 105.3 +/-86.1 mg in 147 of 249 noncritical patients (59.0%) reduced mortality and shortened duration of hospitalization, while 121 of 152 critical patients (79.6%) received corticosteroids at a mean daily dose of 133.5 +/-102.3 mg, and 25 died 25 . A subsequent retrospective observational study of 309 MERS patients showed that those who received high dose steroids were more likely to require mechanical ventilation, vasopressors and RRT 26 .…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…In a retrospective study of patients with SARS-CoV and sepsis, steroids, in a mean daily dose of 105.3 +/-86.1 mg in 147 of 249 noncritical patients (59.0%) reduced mortality and shortened duration of hospitalization, while 121 of 152 critical patients (79.6%) received corticosteroids at a mean daily dose of 133.5 +/-102.3 mg, and 25 died 25 . A subsequent retrospective observational study of 309 MERS patients showed that those who received high dose steroids were more likely to require mechanical ventilation, vasopressors and RRT 26 .…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Retrospective analysis of SARS‐CoV patients showed no benefit of corticosteroid administration except when critical cases were analyzed alone and death‐related variables were adjusted. Among these critical patients, corticosteroid therapy did significantly reduce case fatality (Chen, ). Similarly, corticosteroids have been used in some MERS‐CoV patients with severe disease (Assiri et al .,; Guberina et al ., ; Memish et al .,; Omrani et al ., ).…”
Section: Mers‐cov Intervention Strategiesmentioning
confidence: 99%
“…In recent years, infectious agents have become the most important factors in ARDS, especially the avian influenza virus and severe acute respiratory syndrome (SARS) coronavirus [5][6][7][8]. CHEN et al [9] investigated the efficacy and safety profiles of corticosteroid therapy in SARS patients, and reported that the proper use of corticosteroids in confirmed critical SARS resulted in lower mortality and shorter hospital stay. MEDURI and co-workers [10,11] reported that prolonged administration of methylprednisolone in patients with unresolving ARDS significantly improved pulmonary and extrapulmonary organ dysfunction and reduced mortality.…”
mentioning
confidence: 99%